Risk of adverse swallowing events and choking during deworming for preschool-aged children. - James Wyatt Kernell; Rosalie V DePaola; Alec M Maglione; Lacey N Ahern; Naomi G Penney; David G Addiss (PLoS Neglected Tropical Diseases)
Background In areas where the prevalence of soil-transmitted helminthiasis (STH) is >20%, the World Health Organization (WHO) recommends that deworming medication be given periodically to preschool-age children. To reduce risk of choking-related deaths in children <3 years old, WHO recommends that deworming tablets be crushed and given with water. Little is known about how widely this is practiced or its effectiveness. Methodology and principal findings Albendazole distributions for STH were observed for children 1-4 years old in 65 sites in India and Haiti. Information was recorded on child demographics; child demeanor immediately before, as well as struggling or resistance during albendazole administration; tablet form (i.e., crushed or not); and adverse swallowing events (ASEs), including choking, spitting; coughing; gagging; vomiting; and expelling a crushed tablet in a "cloud" of powder. Of 1677 children observed, 248 (14.8%) had one or more ASEs. ASE risk was 3.6% with whole tablets, 25.4% with crushed tablets, and 34.6% when crushed tablets were mixed with water. In multivariate analysis, ASE risk was significantly associated with children 1 year (OR 2.7) or 2 years (OR 2.9) of age; male gender (OR 1.6); non-content child demeanor (fearful, fussy, or combative) before albendazole administration (OR 4.3); child struggling when given albendazole (OR 2.1); and giving water, either after the tablet or mixed with it (OR 5.8). Eighteen (1.1%) children choked, none fatally; 17 choking incidents occurred with crushed tablets. In a multivariate analysis that controlled for distribution site, the only significant risk factor for choking was non-content demeanor (OR 20.6). Conclusions and significance Deworming-related choking deaths in young children are preventable. In our sample, risk of choking could have been reduced by 79.5% if deworming tablets were not given to young children who were fussy, fearful, or combative or who struggled to resist tablet administration, with only an 18.4% reduction in drug coverage.